Energy transducing redox steps of the Na(+)-pumping NADH:quinone oxidoreductase from Vibrio cholerae - Juárez, Oscar (National Academy of Sciences, 2010)
Na(+)-NQR is a unique respiratory enzyme that couples the free energy of electron transfer reactions to electrogenic pumping of sodium across the cell membrane. This enzyme is found in many marine and pathogenic bacteria where it plays an analogous role to the H(+)-pumping complex I. It has generally been assumed that the sodium pump of Na(+)-NQR operates on the basis of thermodynamic coupling between reduction of a single redox cofactor and the binding of sodium at a nearby site. In this study, we have defined the coupling to sodium translocation of individual steps in the redox reaction of Na(+)-NQR. Sodium uptake takes place in the reaction step in which an electron moves from the 2Fe-2S center to FMN(C), while the translocation of sodium across the membrane dielectric (and probably its release into the external medium) occurs when an electron moves from FMN(B) to riboflavin. This argues against a single-site coupling model because the redox steps that drive these two parts of the sodium pumping process do not have any redox cofactor in common. The significance of these results for the mechanism of coupling is discussed, and we proposed that Na(+)-NQR operates through a novel mechanism based on kinetic coupling, mediated by conformational changes.